THE MANIFESTATION OF THE RECHTSIDEE OF PANCASILA IN REGULATING THE CONSTITUTIONAL RIGHTS IN INDONESIA - A. Ahsin Thohari (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2019)
Abstract: Pancasila is the ideal of the state (staatsidee). It also serves as legal ideal (rechtsidee), fundamental of philosophy (philosofische grondslag), fundamental state norm (staatsfundamentalnorm), and view of life (weltanschauung). It is a flexible ideology that can be drawn, pressed, and broaden to cover almost all circumstances. The perspective and mindset forming the constitution concerning human rights, and citizen constitutional rights had changed due to the changes in worldview attitudes, internationalism, and cosmopolitanism about human and constitutional rights. The constitution in Indonesia had changed several times. However, the provision of the civil rights in the Indonesian constitutions or known as constitutional rights were not eliminated in the 1945 Constitution (since august 18th 1945), the 1949 Union Republic of Indonesia Constitution, the 1950 Temporary Constitution, the 1945 constitution (after the President Decree in July 5th,1959) and 1945 constitution after amendment. Pancasila, also known as five principles, has the function as the bedrock of Indonesia. However, as a philosophical principle, Pancasila can interpret in myriad perspective, potentially used for multiple purposes. Abstrak: Pancasila sebagai cita negara (staatsidee). Pancasila yang juga berfungsi sebagai cita hukum (rechtsidee), dasar filsafat (philosofische grondslag), norma fundamental negara (staatsfundamentalnorm), dan pandangan hidup (weltanschauung). Pancasila adalah ideologi yang bersifat fleksibel yang dapat ditarik, ditekan, dan dilebarkan untuk mencakup hampir semua keadaan. Cara pandang dan pola pikir pembentuk Undang-Undang Dasar (UUD) terhadap Hak Asasi Manusia, konstitusi, dan hak-hak konstitusional warga negara mengalami perubahan yang diakibatkan oleh perubahan sikap-sikap pandangan dunia, internasionalisme dan kosmopolitanisme tentang HAM dan hak konstitusional. Konstitusi di Indonesia telah mengalami beberapa kali perubahan, namun ketentuan-ketentuan tentang hak-hak warga negara dalam konstitusi-konstitusi Indonesia atau yang lebih dikenal dengan hak konstitusional tidak pernah hilang, baik dalam UUD 1945 yang berlaku mulai 18 Agustus 1945, Konstitusi RIS 1949, UUDS 1950, UUD 1945 setelah Dekrit Presiden tanggal 5 Juli 1959, dan UUD 1945 setelah Perubahan. Pancasila, yang juga dikenal sebagai lima prinsip, berfungsi sebagai landasan negara Indonesia. Namun, sebagai prinsip filosofis, pancasila dapat ditafsikan ke berbagai perspektif yang dapat digunakan untuk berbagai tujuan. Kata Kunci: Cita Hukum (Rechtsidee), Pancasila, Hak Konstitusional